2012
DOI: 10.1182/blood-2011-11-390989
|View full text |Cite
|
Sign up to set email alerts
|

The clinically active BTK inhibitor PCI-32765 targets B-cell receptor– and chemokine-controlled adhesion and migration in chronic lymphocytic leukemia

Abstract: Small-molecule drugs that target the B-cell antigen receptor (BCR) signalosome show clinical efficacy in the treatment of B-cell non-Hodgkin lymphoma. These agents, including the Bruton tyrosine kinase (BTK) inhibitor PCI-32765, display an unexpected response in patients with chronic lymphocytic leukemia (CLL): a rapid and sustained reduction of lymphadenopathy accompanied by transient lymphocytosis, which is reversible upon temporary drug deprivation. We hypothesized that this clinical response reflects impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
422
3
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(443 citation statements)
references
References 27 publications
15
422
3
3
Order By: Relevance
“…In addition, prominent intracellular signaling is observed in CLL cells from or egressing from lymph node, suggesting that lymph nodes are sites of survival and proliferative stimulus [72]. As a consequence, ibrutinib treatment, which inhibits BCR signaling, leads to a transient increase in circulating CLL cells concurrent with the reduction in lymphadenopathy [75][76][77].…”
Section: Implication Of the Bcr Tlr Pathwaysmentioning
confidence: 99%
“…In addition, prominent intracellular signaling is observed in CLL cells from or egressing from lymph node, suggesting that lymph nodes are sites of survival and proliferative stimulus [72]. As a consequence, ibrutinib treatment, which inhibits BCR signaling, leads to a transient increase in circulating CLL cells concurrent with the reduction in lymphadenopathy [75][76][77].…”
Section: Implication Of the Bcr Tlr Pathwaysmentioning
confidence: 99%
“…In preclinical models, ibrutinib induced apoptosis and decreased survival of CLL cells and inhibited their homing, migration, and adhesion to the tumor microenvironment. [18][19][20] Recently, in the phase 3 RESONATE trial (PCYC-1112-CA) in relapsed/refractory CLL, ibrutinib demonstrated a statistically significant 78% reduction in the risk of progression or death and a 56% reduction in the risk of death compared with ofatumumab. 21 Ibrutinib was US Food and Drug Administration-approved for treatment of patients with CLL who received $1 prior therapy and for patients with CLL with del (17)(p13.1).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical models demonstrated that ibrutinib inhibits CLL cell survival and proliferation (9), as well as leukemia cell migration toward tissue-homing chemokines (CXCL12, CXCL13) and integrin-mediated CLL cell adhesion (10,11). For patients with CLL, ibrutinib is given orally as a once-daily fixed dose of 420 mg on a continuous schedule until progression or toxicity.…”
mentioning
confidence: 99%